Sensorimotor impairments of paretic upper limb correlates with activities of daily living in subjects with chronic stroke - Ng S.M. Shamay; Tsang W.N. William; Kwong W.H. Patrick; Tse T.F. Philip; Wong C.H. Jefferry (AOSIS, 2011)
The  main objective  of  this  study  was  to  investigate  the correlations  between sensorimotor  impairments  of  paretic  upper  limb  and the  hand  functions of  activities of daily  living  (ADLs)  scores  in  persons  with chronic stroke.This is a cross-sectional  study  with  19  chronic  stroke  survivors.  Hand function was measured by the Jebsen-Taylor Hand Function Test (JTHFT). Impairments in upper extremity motor function were measured by upper limb items  of  Fugl-Meyer  Assessment  (FMA-UE).  Forearm  muscles  strength, handgrip  and  pinch  grip  power  were  assessed  using  handheld  dynamo-meters. Tactile sensation threshold was measured by monofilaments.Significant differences were found between the affected and unaffected side in the total JTHFT scores, forearm muscle strength, handgrip and pinch grip (p≤0.017), but not the tactile sensa-tion threshold.  The total JTHFT scores were found to be correlated with total score of FMA-UE (rs = -0.789), hand-grip  power  (rs = -0.588) and pinch grip power (rs = -0.657) on the affected side, but not the tactile sensation. The total JTHFT scores were correlated with FMA-UE scores, handgrip and pinch grip of the affected side.  This is the first study in documenting the correlation between the sensorimotor impairments and JTHFT scores in persons with  chronic stroke. Our findings highlights the importance of including upper limb and grip strength training in stroke rehabilitation program in order to improve hand functions in activities of daily living in patients with chronic stroke.